Axial and radial crushing behaviour of thin-walled carbon fiber-reinforced polymer tubes fabricated by the real-time winding angle measurement system - Ma, Quanjin; Mohd Ruzaimi, Mat Rejab; Mohammad, Azeem; Mat Sahat, Idris; M.F., Rani; Kumar, A.Praveen (Elsevier B.V., 2023)
This paper proposed a real-time winding angle measurement device embedded in the portable 3-axis winding machine, which was used to detect and measure the winding angle during the winding process. The device was completely designed, fabricated, tested, and divided into hardware and software sections. The hardware section was adopted Raspberry Pi 3B+ and Arducam 5MP OV5647 camera modules, and the software section was used the OpenCV software. The experimental test was carried out to validate the measurement data on ±45°, ±60°, and ±75° winding angles, and filament-wound carbon fiber-reinforced polymer tubes were performed the quasi-static radial and axial compression tests. It was found that the real-time measurement data from the system had approximately 0.45±0.02 comparative error value than the targeted winding angle, which was more accurate than traditional measurement data. Moreover, it was shown that peak crushing loading significantly increased with increasing winding angle under radial compression, which had the inverse decreasing trend under axial loading. In addition, the crushing behaviour of thin-walled CFRP tubes was studied.